(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the analgesic efficacy of Nefopam and Ketorolac administered via patient-controlled intravenous analgesia after cesarean section at Hanoi Obstetrics and Gynecology Hospital during 2024-2025. Subjects and methods: A controlled clinical intervention was conducted on 60 parturients who underwent cesarean section under spinal anesthesia at Hanoi Obstetrics and Gynecology Hospital from September 2024 to June 2025. Results: The two study groups were homogeneous in clinical characteristics. The analgesic efficacy of Nefopam and Ketorolac was found to be equivalent at all evaluated time points, with mean VAS scores maintained at a mild pain level (≤ 2 points) after 24 hours. The total patient-controlled intravenous analgesia dose consumed after 48 hours showed no statistically significant difference between the two groups (Nefopam group 105.16 ± 46.75 mg vs. Ketorolac group 106.83 ± 45.98 mg, p ≈ 0.52). Patient satisfaction rates were also comparable (76.7% in the Nefopam group vs. 80.0% in the Ketorolac group, p = 1.000). Conclusion: The use of Nefopam and Ketorolac alone in patient-controlled intravenous analgesia provides equivalent postoperative analgesic efficacy after cesarean section, achieves high patient satisfaction, and eliminates the need for Morphine rescue.